2014
DOI: 10.1007/s10072-014-1782-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, pathological features and surgical outcomes of focal cortical dysplasia (FCD) type II: correlation with pathological subtypes

Abstract: Focal cortical dysplasia (FCD) type II is a major cause of drug-resistant epilepsy. In order to gain insight into the possible correlations between FCD II pathological pattern and different clinical characteristics (including clinical information, imaging characteristics and surgical outcomes), different clinicopathological characteristics in two types of FCD II were analyzed (especially in FCD IIb). The mean age of seizure onset and disease duration of 78 patients was 11.0 and 11.2 years, respectively. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Compared with other FCDs without the TMS, the presence of the TMS indicated a high likelihood of a seizure-free outcome. 20,21 Detecting these lesions during a preoperative examination is important for surgical decision-making and improving postoperative outcomes. 1,22,23 If the preoperative MR imaging indicates type IIb, a favorable prognosis can be expected after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other FCDs without the TMS, the presence of the TMS indicated a high likelihood of a seizure-free outcome. 20,21 Detecting these lesions during a preoperative examination is important for surgical decision-making and improving postoperative outcomes. 1,22,23 If the preoperative MR imaging indicates type IIb, a favorable prognosis can be expected after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the extent of the lesion is smaller than the other epileptogenic tumors. Focal cortical thickening, blurry gray white matter interface, focally increased signal on T2WI and the "transmantle" sign are the MR characteristics of FCD [11,12]. Interestingly, FCD Ib was observed in the transition region in one of our cases, which might imply the homogeneous genetic origination of PLNTY and FCD.…”
Section: Discussionmentioning
confidence: 52%
“…The study by Simpson and Prayson, taking into consideration the ILAE classification, including the new FCD IC subtype, did not reveal any differences in Engel I rate after surgery, which was 48%, in all three FCD I subtypes (82). The outcome in FCD II cases is better, it fluctuates between 50-88% (40,71). There is a higher seizure outcome in FCD IIB, compared to FCD IIA, and there is no correlation between outcome and age at onset or the duration of epilepsy (71).…”
Section: Clinicopathological Associations and Outcomementioning
confidence: 87%
“…Adult-onset epilepsy in most studies is limited to several cases (38,39). Seizures are generally of high frequency, up to dozens a day (40) and can be localised or generalise secondarily. A recent study comparing the characteristics of patients with FCD and epilepsy onset in the first year showed that the presence epileptic spasms is connected with the frontal lobe localisation of the lesion (41).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation